Pengaruh Penerapan Gaya Mengajar Komando Terhadap Gerak Dasar Servis Panjang Dalam Permainan Bulutangkis Pada Siswa SMP Negeri 3 Tondano - Natasya Momintan; Drs. Dj. A. Sungkudon M.Kes AIFO; Dr. Jan Lengkong M.Kes AIFO (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This research aims to examine the influence of the command teaching style on students' long service skills in badminton games at SMP Negeri 3 Tondano. The study employed an experimental design with a randomized control group using pre-test and post-test assessments. The participants consisted of 22 students divided into experimental and control groups, each comprising 11 students. Data were gathered using a long service skill test. The results of the t-test analysis showed a significant difference, with tcount = 8.28 exceeding ttable = 2.086. These findings indicate that the command teaching style effectively enhances students' long service abilities in badminton.